A novel variant of GLI3, p.Asp1514Thrfs*5, is identified in a Chinese family affected by polydactyly. Issue 7 (12th May 2022) - Wang, Yusi; Hao, Xuguang; Jia, Xueyuan; Ji, Wei; Yuan, Shuai; Gnamey, Estelle Judith Abla; Huang, Min; Xu, Lidan; Zhang, Xuelong; Bai, Jing; Sun, Wenjing; Fu, Songbin; et al.
Abstract: Background: Polydactyly is a common congenital malformation characterized by the presence of supernumerary fingers or toes. In this case study, we sought to identify the causative pathogenic factor in a family from a northern region of China affected by non‐syndromic postaxial polydactyly (PAP). Methods: After recruiting a three‐generation family with PAP, whole‐exome sequencing was performed to identify the causative variant. In silico analysis and Sanger sequencing were used to validate the variant. Results: We identified a novel heterozygous frameshift variant (NM_000168.6:c.4540delG, p.Asp1514Thrfs*5) in the transcriptional activator (TA1) domain of the GLI3 gene. Conclusion: The novel frameshift variant identified in this study further confirms the relationship between non‐syndromic PAP and GLI3 and extends the previously established mutational and phenotypic spectra of GLI3 . Abstract : This paper clearly introduces the pathogenic variation sites of this family and provides targeted analysis and genetic counseling for the family.